Effect of cisapride on the gastrointestinal transit of a solid meal in normal human subjects. Issue 1 (January 1987) - Edwards, C A; Holden, S; Brown, C; Read, N W
Abstract : The effect of cisapride, a new gastrointestinal prokinetic agent, on the transit of a standard meal through the stomach, small intestine and colon was studied in 10 normal subjects. Cisapride had no significant effect on gastric emptying but decreased mouth to caecum transit time (p less than 0.01). Stool weight and frequency were not significantly increased but the time for the first appearance of stool markers and the arrival of 20% and 50% of stool markers was decreased after cisapride (p less than 0.05).